SMALL AND MEDIUM-SIZED ENTERPRISES: ANALYSIS OF TRENDS AND ASSESSMENT OF PREREQUISITES FOR ENHANCING INNOVATIVE DEVELOPMENT (Development Service Industry Management, 2024)
The key trends in the development of the entrepreneurial environment of small and medium-sized businesses are analysed. The prerequisites for enhancing the innovative development of small and medium-sized enterprises in modern economic conditions are assessed. Three groups of countries differing in the parameters of the representation of performance indicators of the small and medium-sized enterprises sector in the overall results of the national economy have been identified. The validity of the assumptions about the predominant orientation of domestic entrepreneurs in the innovation sphere, primarily to the implementation of innovative solutions, which are determined by a relatively short-term horizon of implementation prospects, reduced needs for the necessary capital investments, and, as a result, limited potentially achievable positive results from implementation, has been confirmed. It is noted that problems in the field of innovative development of the domestic business sector are determined by the long-term and systemic nature of manifestation. The basic properties inherent in the processes of digitalisation of small and medium-sized businesses in modern economic conditions are defined. It is noted that it is at the entrepreneurial level of the economic system a conscious request of small and medium-sized businesses for the generation of innovations should be formed, the introduction of which, in order to strengthen the competitive advantages of national producers, will determine the need to create appropriate institutional, organisational and other prerequisites for enhancing innovative development at the sectoral and regional levels. It is determined that one of the key tasks for intensifying innovation activity is to ensure a high level of receptivity and readiness of small and medium-sized businesses to generate, select, implement and successfully use innovations.
Keywords: business; small and medium-sized enterprises; trends; prerequisites; enhancing; innovative development